Vacancy ordered γ-Fe 2 O 3 nanoparticles functionalized with nanohydroxyapatite: XRD, FTIR, TEM, XPS and Mössbauer studies - Ramos Guivar J.A. (2016)
Vacancy ordered maghemite (γ-Fe2O3) nanoparticles functionalized with nanohydroxyapatite (HAp – Ca10(PO4) 6(OH)2) have been successfully synthesized using an inexpensive co-precipitation chemical route. Evidence for the presence of vacancy order in maghemite was shown by the superstructure lines observed in X-ray diffraction. The adsorption of carboxyl groups of citric acid (C6H8O7) onto γ-Fe2O3 nanoparticles was investigated by FTIR, XPS and Mössbauer spectroscopy. From XPS surface analysis, two binding energies related to oxygen were attributed to bindings between C6H8O7/γ- Fe2O3 and C6H8O7/HAp from an interfacial reaction promoted by strongly adsorbed H2O molecules at the surface of these nanomaterials.